Development and preliminary validation of the Coach Interpersonal Style Observational System - Pulido, J. J.; Sánchez-Oliva, D.; Silva, M. N.; Palmeira, A. L.; Garcia-Calvo, T. (International Journal of Sports Science & Coaching, 2019)
Objectives: The aim of this study was to design and develop a multidimensional observational coding system (Coach Interpersonal Style Observational System) to assess coaches' interpersonal style adopted during training sessions and matches. Equipment and methods: Content validity was established by 11 experts (with proven knowledge and experience in sport science, motivational psychology, and coaching) using qualitative (e.g. ease of comprehension, utility, and adequacy of examples) and quantitative (category scores) approaches. Coders were trained to test inter- and intra-rater reliability. Results: Qualitative analyses revealed global positive assessment. Experts' category scores were very high. After coder training, inter- and intra-rater reliability scores were acceptable. Discriminant validity was tested through the pilot application to eight soccer coaches. Overall, the results support the preliminary reliability and validity of an instrument to analyze interpersonal coach behavior.